A study on optical, morphological and mechanical properties of Al2O3 ultra-thin films deposited by RF reactive magnetron sputtering. (2015) - Pat, Suat; Özen, Soner; Şenay, Volkan; Aydoğmuş, Tuna; Elmas, Saliha; Korkmaz, Şadan; Ekem, Naci; Balbağ, M. Zafer
The Al2 O3 ultra-thin films with the thicknesses of 30 nm and 35 nm were deposited on glass microscope slides by a radio frequency reactive magnetron sputtering system. The optical, morphological and mechanical properties were investigated as function of the film thickness. The refractive index of the resulting Al2 O3 ultra-thin film increased with the increasing thickness. Both the films showed high transparency of > 85% and low reflectivity of < 10% in the visible and near infrared region. A band gap of ∼8.65 eV was obtained for the 30 nm film and ∼7.53 eV for the 35 nm film from an empirical relation between refractive index and band gap. According to the results obtained from the AFM studies, the root mean square surface roughness of the films are 3.67 nm and 3.77 nm for the 30 nm and 35 nm film, respectively. The hardness and Young modulus values decreased with the increasing film thickness.